(Semi)peripheries in contact - Allwood, Anja (Stridon, 2021)
This article widens the perspective of indirect translation (ITr) research by focusing on the range of mediating languages and with a corpus of all indirect translations into a specific language (Swedish) during 2000-2015. The following issues will be described and explained: which languages are used as mediating languages (MLs), what their respective proportions look like, and which possible rea-sons for using a language other than English as the ML can be identified. The corpus reveals that out of all novels translated into Swedish during the period under study, 1.3% (70 novels) were indirect translations, and out of these 70, more than two thirds have English as the ML. A search into the cases where English has not been used produced a list of suggested reasons regarding the choice of ML. The most often occurring explanation seems to be that no English translation existed, or thatsuch a translation was already indirect.
Keywords: indirect translation; literarni prevod; literary translation; novels; posredni prevod; romani; Swedish language; švedski jezik; triangualcija; triangulation